Comparative metabolic changes of tissues and plasma in breast cancer patients / Erda Syerena Rosli - Rosli, Erda Syerena (2015)
Breast cancer is a common disease and one of the leading causes of cancer death among women in Malaysia. Indeed, in spite of the continual research for the development of this fatal disease, the effort is hampered due to lack of understanding on the pathophysiological of the heterogenous nature of breast cancer. Therefore, metabolomics platform has been used to study the alterations of metabolic pathways which are involved in the disease state. This study aimed to discover the metabolic profiles as well as some potential biomarkers of breast cancer patients in different stages of the disease. Hence, global metabolite profiling was used. Plasma samples of 22 breast cancer patients and healthy volunteers were compared. In addition, tumour tissue and normal tissue of 12 breast cancer patients were analysed. Samples were subjected to Liquid Chromatography Mass Spectrometry Time of Flight (LCMS/QTOF). Method optimization using different extraction solvents was performed. Significant analysis (corrected p-value, p<0.05) and fold change analysis (FC^2.0) were done. All detected metabolites that have passed through applicable statistical methods were treated as potential biomarkers and were used for differential analysis. In the comparison between breast cancer patients and healthy volunteers, maltose and hypoxanthine which are involved in energy production and deoxyribonucleic acid (DNA) synthesis pathway were reported with the highest AUC value of 0.941 and 0.898, respectively. On the other hand, most fatty acids and lipid metabolites were significantly perturbated in tumour samples when compared to normal tissue samples. This relates to their importance in proliferation of cancer cells. Meanwhile, based on the patient’s estrogen receptor (ER) status, xanthine and hypoxanthine were observed to be down-regulated in ER negative tumour tissues compared to ER positive. On the other hand, spermine was up-regulated in ER negative tumour tissues. In tumour tissue grading status results, eicosanoid metabolites and spermine were found to be significantly different. From the finding, disruption of spermine in ER status and grading status of tumour tissues can be subjected to the degree of aggressiveness in tumour progression. Based on the results, we believed that these “potential biomarkers” can possibly be used as biomarkers for further study to improve the diagnosis and therapeutic strategy for breast cancer.